Pediatric primary cutaneous anaplastic large cell lymphoma treated with brachytherapy. Issue 3 (19th March 2021) - Linggonegoro, Danny W.; McCormack, Lindsay; Grenier, Pierre‐Olivier; Vrooman, Lynda M.; Devlin, Phillip M.; Huang, Jennifer T.
Abstract: Primary cutaneous anaplastic large cell lymphoma (PC‐ALCL) is a CD30+ lymphoproliferative disorder that rarely occurs in children. Although there are currently no consensus guidelines for the treatment of cutaneous lymphoma in the pediatric population, the isolated form of PC‐ALCL is typically managed by surgical excision or external beam radiation therapy. We report the case of a 6‐year‐old girl with primary cutaneous anaplastic large cell lymphoma that was treated with brachytherapy with no recurrence after 21 months of follow‐up, suggesting that brachytherapy may be considered as a treatment for pediatric cutaneous large cell anaplastic lymphoma.